Analysis of vehicle ride comfort applying a 2SPS+SR parallel seat mechanism. (April 2021) - Yan, Bijuan; Zhang, Jie
The violent vibration may cause discomfort to the driver and operation instability in different directions including fore-aft, lateral, and vertical when construction vehicles are driven or operated on off-roads. To improve ride comfort, a novel kind of 2SPS+SR parallel seat mechanism is proposed in this article. First, to verify the motion state of one translation and two rotations, the model of this new seat mechanism was built and analyzed using UG software. Furthermore, the acceleration and power spectrum density between the conventional seat and the 2SPS+SR parallel seat were compared in three directions of vertical, pitching, and rolling when the vehicle was driven on different three-dimensional roads. Then, the comparisons of the weighted vibration level and the root mean square of the total weighted acceleration on different roads were illustrated to denote the ride comfort of the construction vehicle. The results show that this 2SPS+SR parallel seat mechanism could improve the ride comfort of construction vehicles. The results will provide theoretical support for further research on the control of vehicle vibration.